2017
DOI: 10.4149/bll_2017_011
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and neonatal outcomes in women with type 1 diabetes mellitus

Abstract: AIM: The aim of study was to compare some perinatal outcomes in mothers with type 1 diabetes mellitus (T1DM). MATERIAL AND METHODS: All patients with T1DM delivered at the 1st Department of Obstetrics & Gynaecology of Faculty of Medicine, Comenius University in Bratislava from January 1st 2009 to December 31th 2015 were included to the study. RESULTS: Out of 118 diabetic mothers, 46.6 % had vasculopathy and 53. 4 % were without microvascular complications. In the vasculopathy group, signifi cantly higher incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Its frequency has been reported between 60% and 78%. [91112] The cesarean ratio was 72% in our cases. Even in the most favorable conditions, a pregnant patient with T1DM is likely to deliver by cesarean section.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Its frequency has been reported between 60% and 78%. [91112] The cesarean ratio was 72% in our cases. Even in the most favorable conditions, a pregnant patient with T1DM is likely to deliver by cesarean section.…”
Section: Discussionmentioning
confidence: 49%
“…[78] It has been reported that preeclampsia developed in 19.1% of patients without vasculopathy and 49.1% of the diabetic patients with vasculopathy. [9] Our preeclampsia cases were not with chronic hypertension. In the cases with chronic hypertension the preeclampsia ratio would be much more higher.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Even in high-risk newborns, the optimal diet is enteral. Since the newborns of mothers without optimal metabolic compensation during pregnancy are at risk of postnatal hypoglycaemia, the initiation of enteral nutrition is desirable also for babies of mothers with diabetes mellitus, (6). By analysing the breast milk, we are able to optimize newborn enteral nutrition with fortifi ers.…”
Section: Introductionmentioning
confidence: 99%
“…The affected newborns may suffer metabolic syndrome, risk of obesity and respiration distress [1,4]. Growing population of infants with metabolic syndrome as a consequence of maternal diabetic condition raises the great concern about cardiovascular disease developed already in adolescents [5].…”
mentioning
confidence: 99%